Association between hypertensive disorders of pregnancy and cardiovascular disease in a population of Cameroonian women at two hospitals of yaounde : a case control study - Ebongué, Mbondji; Nguimbis, Benedict (My University, 2018)
Background: Positive associations have been found between Hypertensive Disorders of Pregnancy gestational hypertension, preeclampsia and cardiovascular diseases within non-black African populations, but no data exist from sub-Saharan Africa. We aimed to assess this association in Cameroonian mothers. Methods: We used a case-control design. Cases were women diagnosed with arteriosclerotic cardiovascular disease between 2012 and 2017 at the General and the Gyneco-obstetric hospital of Yaoundé. Controls were mothers of children who seeked pediatric care at the Gyneco-obstetric hospital of Yaoundé, with no diagnosis of cardiovascular disease. We abstracted data from patient files to assess cardiovascular disease, and used phone-based questionnaires to assess prior history of Hypertensive Disorders of Pregnancy. We used logistic regression and propensity scores for adjustment. Results: Out of 1228 individuals selected, 173 cases and 339 controls participated in the study. We found no increased risk of cardiovascular diseases for women with a history of Hypertensive Disorders of Pregnancy (OR = 0.83, 95% CI, 0.51 to 1.34). Women with gestational hypertension had 2.33 (95% CI, 0.99 to 5.50) times the risk of women with no history of Hypertensive Disorders of Pregnancy, an inverse association was observed between preeclampsia and cardiovascular diseases (OR = 0.28, 95% CI, 0.10 to 0.72). Conclusions: Cameroonian women with a history of gestational hypertension may have an increased risk of cardiovascular diseases. However, population-based studies with more accurate data on the exposure are needed.
Supplemental Materials: https://osf.io/xv4dz/
Keywords: Cardiovascular diseases; gestational hypertension; Hypertensive disorders of pregnancy; preeclampsia